2022
DOI: 10.3748/wjg.v28.i27.3359
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic surgery to treat hepatopancreatobiliary cancer: A technical review

Abstract: Single-incision laparoscopic surgery (SILS), or laparoendoscopic single-site surgery, was launched to minimize incisional traumatic effects in the 1990s. Minor SILS, such as cholecystectomies, have been gaining in popularity over the past few decades. Its application in complicated hepatopancreatobiliary (HPB) surgeries, however, has made slow progress due to instrumental and technical limitations, costs, and safety concerns. While minimally invasive abdominal surgery is pushing the boundaries, advanced laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…Additionally, laparoscopic surgery provides a clearer surgical field of view, facilitating the surgeon's assessment of the patient's visceral peritoneum, mesentery and other tissues. It also allows for more precise approach selection, reducing unnecessary tissue damage and thus preserving patients' postoperative sexual function while lowering the risk of postoperative complications [18]. In this study, we observed that using SILS + 1 for the treatment of sigmoid colon cancer resulted in postoperative urinary function, sexual function, and complication rates similar to those achieved with CLS, thereby highlighting the safety and feasibility of SILS + 1.…”
Section: Discussionsupporting
confidence: 54%
“…Additionally, laparoscopic surgery provides a clearer surgical field of view, facilitating the surgeon's assessment of the patient's visceral peritoneum, mesentery and other tissues. It also allows for more precise approach selection, reducing unnecessary tissue damage and thus preserving patients' postoperative sexual function while lowering the risk of postoperative complications [18]. In this study, we observed that using SILS + 1 for the treatment of sigmoid colon cancer resulted in postoperative urinary function, sexual function, and complication rates similar to those achieved with CLS, thereby highlighting the safety and feasibility of SILS + 1.…”
Section: Discussionsupporting
confidence: 54%
“…With the development of technology, at present, the LAP has been applied to tumors in the entire liver are, and has become one of the standard treatments for resection of the right anterior and left lateral lobes. A large number of studies have confirmed the safety and feasibility of LAP (36,37). Compared with OPEN, LAP has the advantages of aesthetics, less blood transfusion, less tissue damage, less patient pain, and shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the widespread application of laparoscopic liver resection, the International Laparoscopic Liver Society was formed in 2016 by a group of experts[ 31 ]. Single-incision and robot-assisted technology are also available for minimally invasive liver surgery[ 32 , 33 ]. Additionally, laparoscopic techniques have achieved great success in the treatment of adrenal, prostate, and rectal diseases, among others[ 34 - 36 ].…”
Section: Application Of Laparoscopic Technique In Surgerymentioning
confidence: 99%